Guideline on Preterm Labor and Delivery by the Society of Specialists in Perinatology (Perinatoloji Uzmanları Derneği-PUDER), Turkey - Altay, M.; Bayram, M.; Biri, A.; Büyükbayrak, E.; Deren, Ö.; Ercan, F.; Eroǧlu, D. (OrtadogÂŸu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S., 2020)
Preterm delivery (PTD) occurs between 200/7-366/7 weeks of pregnancy and is a major cause of perinatal mortality and morbidity. The prevalence is around 12% in Turkey, ranging between 10 to 15% in different centers. Indicated preterm deliveries due to maternal or fetal reasons constitute approximately 20-30% of the total. The rest occur as a result of spontaneous preterm labor (PTL) or preterm prelabor rupture of the membranes (PPROM), about half and half. Although etiology of spontaneous preterm birth has not been fully elucidated, several risk factors are defined. History of PTD and short cervix are two most important risk factors, particularly in singleton pregnancies. If the cervical length is measured to be <25 mm via transvaginal ultrasonography before the 32nd gestational week, it is defined as short cervix. In women with prior PTD, progesterone preparations are recommended between 16th-36th gestational weeks and cervical length is monitorized; additional preventive measures may be required if short cervix is diagnosed. In women without prior PTD, we universally offer transvaginal ultrasonographic cervical length measurement at the time of midtrimester fetal anomaly scan. When short cervix is determined in such cases, cervical cerclage, vaginal progesterone, cervical pessary, alone or in combination, may be recommended depending on the measurement and the gestational age. Asymptomatically dilated cervix, PTL, and PPROM are generally managed according to the gestational age on a case-by-case basis. Data are limited in twin and higher order multiple pregnancies to recommend standart prevention and management protocols. © 2020 Journal of Clinical Obstetrics and Gynecology. All rights reserved.
Keywords: Obstetric Labor; Premature; Premature Birth; Preterm Premature Rupture of the Membranes